UPAYA KEPALA MADRASAH DALAM MENINGKATKAN KREATIFITAS GURU DALAM MENANAMKAN NILAI-NILAI AKIDAH AKHLAK PESERTA DIDIK DI MADRASAH ALIYAH AL-IHSANIYAH MUARO JAMBI - Muamar Muamar; Ida Riyanti; Abdullah Yunus (STKIP Subang, 2024)
This study aims to find out: 1. 1. The process of the head of the madarasah in planning teachers to be creative; 2. Factors that inhibit madrasah heads in increasing the creativity of moral faith teachers to instill moral faith values in students; 3. The efforts of the head of the madrasah in increasing the creativity of teachers of moral beliefs instills the values of moral beliefs in students. This research makes qualitative research using the right approach. This study uses documentation, observation, and interviews as data collection methods. The data analysis method develops through the process of data reduction, data visualization, formulation and validation of conclusions. Data triangulation is applied in the assessment of validity data. The results of the research are: 1. The process of the head of the madrasah in planning teachers to be creative is fairly good. 2. Factors that inhibit madrasah heads in increasing the creativity of teachers of moral beliefs include: a. Teacher qualifications that are not optimal, b. Teachers' IT skills that are not optimal, c. Inadequate school funds. 3. Efforts made by the head of the madrasah in increasing the creativity of teachers of moral beliefs to instill the values of moral beliefs in students, including: a. Carry out teacher training, b. Conducting supervision, and c. Giving rewards.